Οι πόλεμοι μεταξύ του Νικηφόρου Φωκά και των Αράβων. - ΤΑΚΙΡΤΑΚΟΓΛΟΥ Κωνσταντίνος (Byzantina Symmeikta, 2015)
This article attempts to present the conflicts between the Byzantines and the Arabs, in the period that Nicephorus Phocas was active on the eastern front. It aims to fill certain gaps in the history of this period in the light of medieval Arabic sources. Arab historiographers and geographers recount the deeds of Nicephorus Phocas, both as Domestic and as Emperor, informing us of how the Islamic world reacted to Byzantium’s renewed aggressiveness. Except for the military sector, historians can benefit from the information provided by the Arabic sources regarding internal affairs of the Byzantien Empire, such as the bad relations of Nicephorus Phocas with the circle of Emperor Romanos II or the active role of the Armenians in the wars of that period. This study focuses also on all the conflicts of Nicephorus Phocas, both with the Hamdanids and with the Arabs of Sicily, but allso on the campaigns against Crete and Cyprus. Particular attention is given to the demeanor of the Byzantine Emperor in these operations, as seen by the Arabic sources. στρατιωτικές συγκρούσεις Βυζαντινών και Αράβων την εποχή του Νικηφόρου Β’ Φωκά (963-969) σύμφωνα με τις αραβικές πηγές.